2011
DOI: 10.3109/0284186x.2010.529821
|View full text |Cite
|
Sign up to set email alerts
|

Family members of cancer patients: Needs, quality of life and symptoms of anxiety and depression

Abstract: The results support the importance of screening needs and psychological distress among family members of cancer patients in all phases of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
143
5
19

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(190 citation statements)
references
References 21 publications
23
143
5
19
Order By: Relevance
“…Supportiveness, mood and partners' health condition seem to be more sternly related to female caregivers' than to male caregivers' psychological well-being (Hagedoorn et al, 2002). Fridriksdottir et al (2011) have studied QOL, anxiety, and depression in family members of cancer patients and found high prevalence of anxiety and depression. The latter mentioned study did not specifically report differences for caregivers when studying patients in curative versus palliative phase.…”
Section: Introductionmentioning
confidence: 99%
“…Supportiveness, mood and partners' health condition seem to be more sternly related to female caregivers' than to male caregivers' psychological well-being (Hagedoorn et al, 2002). Fridriksdottir et al (2011) have studied QOL, anxiety, and depression in family members of cancer patients and found high prevalence of anxiety and depression. The latter mentioned study did not specifically report differences for caregivers when studying patients in curative versus palliative phase.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies the proportion of above cut-off scores (≥ 11) varied between 7% -40% for anxiety and 5% -12% for depression (Price et al, 2010;Gough & Hudson, 2009;Janda et al, 2008;Friðriksdóttir et al, 2011). A quite comparable study found 16% of caregivers to be anxious (cut-off ≥ 11) and 11% to be depressed (cut-off ≥ 9) (Zwahlen et al, 2008).…”
Section: Main Issues Of Caregivers' Psychosocial Distressmentioning
confidence: 89%
“…Ansiedad: Inventario de ansiedad: rasgo-estado (IDARE): estado (mínima 36-44, leve 45-52, moderada 53-61 y severa 62-79), rasgo (mínima 23-31, leve 32-37, moderada 38-43 y severa 44-68) (30,31) . Para evaluar ambos Escala de ansiedad y depresión hospitalaria (HADS) (32) y el Perfil de estado de ánimo (POMS (33) Para carga se recomienda la Caregiver Reaction Assessment (CRA) (34) y la Escala de Carga del Cuidador de Zarit (ECCZ) (35,36) (47-54 sobrecarga leve, 55 o más sobrecarga intensa).…”
Section: Evaluaciónunclassified